Development of ultra-low volume, multi-bio fluid, cortisol sensing platform. Issue 1 (December 2018) - Upasham, Sayali; Tanak, Ambalika; Jagannath, Badrinath; Prasad, Shalini
Abstract The development of a non-faradaic electrochemical sensor for screening across multiple bio-fluids that demonstrate the expression of cortisol using a gold microelectrode-based sensor is reported in this paper. Room temperature ionic liquid (RTIL), BMIM[BF4 ] was used as the buffer to modulate the electrical double layer (EDL) to enhance the electrochemical signal response of the sensor. The sensor design and the surface chemistry was optimized using COMSOL Multiphysics software simulations and FTIR respectively. The sensor was designed so that it uses ultra-low volumes between 3–5 µL of bio-fluid for detection. Cortisol detection was achieved in the physiologically relevant ranges when tested in serum, blood, sweat, and, saliva using non-faradaic Electrochemical Impedance Spectroscopy (EIS) and performance parameters of the sensor were determined. Sensor's response was tested against the only commercially available salivary cortisol point-of-care kit using regression analysis. Cross-reactive studies using prednisone indicated that the sensor is specific for cortisol. The sensor displayed a correlation value i.e. R2  > 0.95 between the signal response and the concentration of cortisol present in the system. Dynamic range of the sensor was across the physiologically relevant range of cortisol i.e. 50–200 ng/ml for serum/blood, 1–40 ng/ml for saliva, and 10–150 ng/ml for sweat. Limit of detection for serum and sweat was 10 ng/ml and 1 ng/ml for saliva.